Pelayanan Publik Berbasis Digital (Implementasi Aplikasi J-Lahbako di Kecamatan Jenggawah Kabupaten Jember) - Mayasiana, Nur Aini; Maharani, Ivana Septia; Munawaroh, Lailatul (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The transformation of electronic public services in Population Administration Data Collection is a necessity because there is a shift in the view that the government that used to be the locus of governing is now focused on community service. Good government (good governance) is the main goal of democratization, in addition to being a development dynamic that refers to the occurrence of social change at the local, national and even global scope. J-Lahbako is the government's breakthrough in efforts to provide population administration and civil registration services that were just launched in February 2022 by the Jember Regency Population and Civil Registration Office. J-Labahko is a service that covers population administration for the Jember community as a whole in Jember Regency down to the village level. Jenggawah District is one of the sub-districts in Jember Regency that has implemented the J-Lahbako application network system. One of the villages in Jenggawah District, namely Kemuningsari Kidul, was the place where the J-Lahbako application was first inaugurated which was attended by all stakeholders in Jember Regency. This research refers to qualitative methods and descriptive approaches, this is to answer any questions that arise in the research. The type of primary data is in the form of data collection through interviews with the Department of Population and Civil Registration, apparatus and the community in Jenggawah District. The J-Lahbako application until March 2023 can be accessed by 175 villages out of 248 villages in Jember Regency or has been realized by 70%. The J-lahbako digital service is effective in assisting the government, namely the Population and Civil Registration Office in providing population administration services to village areas, however there are several obstacles including frequent system disruptions and limited knowledge of J-lahbako operators regarding changes to rules in the J-lahbako system.